2005
DOI: 10.1002/gps.1325
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of donepezil in patients with more severe Alzheimer's disease: a subgroup analysis from a randomized, placebo‐controlled trial

Abstract: In this analysis, donepezil had significant benefits over placebo on global, cognitive, functional, and behavioral measures in a subgroup of patients with more severe AD. Furthermore, the treatment effects of donepezil were not driven by a particular stratum within the moderate to severe dementia range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 45 publications
2
94
0
1
Order By: Relevance
“…These observations are consistent with the effects of donepezil 10 mg/ day in other studies in patients with severe AD [6,7,19] . Cognition in patients with severe AD receiving 5 mg/day treatment improved significantly.…”
Section: Discussionsupporting
confidence: 82%
“…These observations are consistent with the effects of donepezil 10 mg/ day in other studies in patients with severe AD [6,7,19] . Cognition in patients with severe AD receiving 5 mg/day treatment improved significantly.…”
Section: Discussionsupporting
confidence: 82%
“…4 The findings of a study showing that combination therapy with memantine and a cholinesterase inhibitor was more effective than treatment with a cholinesterase inhibitor alone 5 have not been replicated. 6 Results from randomized, controlled trials involving patients with moderate-to-severe 7,8 or severe [9][10][11][12] Alzheimer's disease suggest that cholinesterase inhibitors are associated with modest improvements in cognition and function, and these drugs are approved by the Food and Drug Administration in the United States for the treatment of severe Alzheimer's disease. All the trials involving patients with severe Alzheimer's disease, however, have involved nursing home residents, and none of the trials focusing on moderateto-severe or severe Alzheimer's disease have investigated the strategy of continuing treatment with cholinesterase inhibitors in patients already taking those drugs.…”
Section: Resultsmentioning
confidence: 99%
“…A multinational study comparing donepezil to placebo in severely ill patients still in the community showed similar findings. 47 In another study 48 involving a population of patients with moderate-to-severe AD (defined as an MMSE score of 5 to 12) but still living in the community, similar dosages of donepezil showed large effects on the SIB (7.42, P = 0.0017) and the MMSE (1.99, P = 0.0022) after 6 months, compared with placebo; equivalent measures of ADL, global change, and the NPI were significantly different. It is thus clear that there may be measurable benefits in treating patients suffering from moderate-to-severe AD with donepezil if they have never had a therapeutic trial with a ChEI.…”
Section: Cholinesterase Inhibitorsmentioning
confidence: 95%